Pengaruh Current Ratio, Return On Equity Dan Debt To Asset Ratio Terhadap Price Book Value Perusahaan Advertising, Printing Dan Media Yang Terdaftar Di Bursa Efek Indonesia - Lidya Novita Anwar; Miftahuddin Miftahuddin; Ihsan Effendi; Yamin Siregar (Universitas Medan Area, 2022)
The purpose of this study was to determine the effect of the current ratio, return on equity and debt to asset ratio on the price book value of advertising, printing and media companies listed on the Indonesia Stock Exchange for the 2015-2019 period. This type of research is associative. Sources of data used in this study are secondary data sources. The population in this study were the financial statements of 19 (nineteen) companies in the advertising, printing and media sub-sectors on the Indonesia Stock Exchange. The sample in this study were 6 (Six) Advertising, Printing and Media Sub-Sector Companies in the Indonesia Stock Exchange with the period 2015-2019. The data collection technique used is documentation. The data analysis technique was performed using SPSS 21.0 for Windows. The results of hypothesis testing show that the Current Ratio (CR) has no significant effect on the Price to Book Value (PBV). Return on Equity (ROE) has a positive and significant effect on Price to Book Value (PBV). Debt to Asset Ratio (DAR) has no significant effect on Price to Book Value (PBV). Current Ratio (CR), Return on Equity (ROE), and Debt to Asset Ratio (DAR) have a significant effect on Price to Book Value (PBV) in 6 (six) Advertising, Printing and Media Sub-Sector Companies on the Indonesia Stock Exchange in 2015 -2019. The value generated in this study is an adjusted R2 value of 0.224 (22.4%) which indicates that the capabilities of the Current Ratio (CR), Return on Equity (ROE), and Debt to Asset Ratio (DAR) models can explain variations in Price to Book Value. (PBV) is 22.4% and the rest is influenced by other independent variables of 77.6%.